(Invited) Characterization of UV Excitation Accelerated Material Changes on as-Grown SiC Epitaxial Layers and Their Impact on Defect Detection. (23rd July 2018) - Das, Hrishikesh; Sunkari, Swapna; Justice, Joshua; Konstantinov, Andrei; Gumaelius, Krister; Svedberg, Jan-Olov; Allerstam, Fredrik
Abstract : Both visible defects and crystal defects in Silicon Carbide (SiC) epitaxial layers are being scanned and identified by in-line production systems. All the modern detection systems use Ultra-Violet (UV) light exposure on the wafers followed by signal capture from topographic and photoluminescence (PL) channels. The repeatability and consistency of these measurements becomes very critical for both determining the quality and yield of the wafers and screening potential affected die for reliability issues. In this work, we present the effects of repeated and long-term UV exposure on the SiC wafers. We document the loss of measurement repeatability and determine the cause for this as a highly accelerated growth of a thin oxide layer. We further offer techniques to recover from this mechanism and offer a way to prevent this from happening. The results are further verified by recreating this mechanism and observing similar effects.